The Effectiveness of Using the Islamic Integration Module on the Critical Thinking Ability of Madrasah Ibtidaiyah Students - Khairiyah, Ummu; Faizah, Silviana Nur (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2019)
This study assesses the effectiveness of the integrated thematic modules of Islamic values on students' critical thinking abilities. The pre-experimental research with One Group Pretest Posttest Design was conducted. The sample was 21 students of Class 3 Madrasah Ibtidaiyah (MI) taken with the saturated sampling technique. Five critical questions were used, namely: (1) formulating the problem, (2) planning a problem-solving strategy, (3) making a decision, (4) analyzing the problem, and (5) evaluating the decision. The data were analyzed descriptively and statistically using paired samples test. The results show that the critical thinking ability was very critical in the category of 48%, critical 24%, quite critical 19%, and less critical 10%. Students' critical thinking abilities have improved after learning using Islamic thematic integration modules (N-gain = 0.5) with the medium category. Statistical test results show that the module has a significant impact (p> 0.05). Based on these results, it can be concluded that the use of integrated thematic modules is effective and can be further implemented.